Rabies Virus Stimulates Nitric Oxide Production and CXC Chemokine Ligand 10 Expression in Macrophages through Activation of Extracellular Signal-Regulated Kinases 1 and 2 - Nakamichi, Kazuo (American Society for Microbiology, 2004)
Macrophages represent an essential part of innate immunity, and the viral infection of macrophages results in the release of multiple proinflammatory mediators, such as nitric oxide (NO), cytokines, and chemokines. This study was undertaken to define the molecular mechanism of macrophage activation in response to rabies virus (RV) infection. In RAW264 murine macrophage cells, a well-characterized macrophage model, RV replication was strictly restricted, whereas cell proliferation was significantly enhanced upon RV inoculation. Transcriptional analyses for the expression of inducible forms of NO synthase (iNOS), cytokines, and chemokines revealed that RV virions potentiate the gene expression of iNOS and CXC chemokine ligand 10 (CXCL10), a major chemoattractant of T helper cell type 1. However, RV stimulation had little or no effect on the expression profiles of proinflammatory cytokines and other types of chemokines. In macrophages stimulated with UV-inactivated RV virions, as well as infectious viruses, the phosphorylation of extracellular signal-regulated kinase (ERK) 1 and 2, members of the mitogen-activated protein kinase family, was significantly induced. Specific inhibitors of MAPK/ERK kinase reduced the RV-induced production of NO and CXCL10. Furthermore, the RV-induced activation of the ERK1/2 pathway was severely impaired by the neutralization of the endosomal and lysosomal pH environment with lysosomotropic agents, indicating that endocytosis is a key step leading to the activation of ERK1/2 signaling. Taken together, these results suggest that the ERK1/2-mediated signaling pathway plays a cardinal role in the selective activation of macrophages in response to RV virions, thereby regulating cellular functions during virus infection.